Composition of the essential oils of three Uzbek Scutellaria species (Lamiaceae) and their antioxidant activities - Mamadalieva, Nilufar Z.; Sharopov, Farukh; Satyal, Prabodh; Wink, Michael (Natural product research, 2017)
The chemical composition of the essential oils obtained from aerial parts of Scutellaria immaculata Nevski ex Juz., Scutellaria ramosissima M. Pop. and Scutellaria schachristanica Juz. (Lamiaceae) growing wild in Uzbekistan was analysed by GC and GC-MS. The main constituents of the essential oils from S. immaculata were acetophenone (30.39%), eugenol (20.61%), thymol (10.04%) and linalool (6.92%), whereas constituents of the essential oils fromS. schachristanica were acetophenone (34.74%), linalool (26.98%) and eugenol (20.67%). The S. ramosissima oil is dominated by germacrene D (23.96%), β-caryophyllene (11.09%), linalool (9.63%) and hexadecanoic acid (8.34%). The essential oils of Scutellaria species exhibited weaker antioxidant effects in DPPH, ABTS and FRAP assays. In FRAP assay, only eugenol exhibited a substantial reducing power IC50 = 2476.92 ± 15.8 (mM Fe(II)/g).
Published online 22 Aug 2016
Gesehen am 01.02.2017